THE GASPORT DOLOMITE IN THE VICINITY OF HAMILTON, ONTARIO - Spurgeon, Ernest S. (My University, 1955)
The Silurian Gasport dolomite member was studied in the Hamilton area. In spite of the mask ing effect of dolomitization, the stratigraphic re lations and results of petrographic and sedimentalogi- cal examination suggest that the depositional locus was that of a shelf or bank. A thin layer of jarosite was observed; further study may show this layer to have important stratigraphic time value.
THE GASPORT DOLOMITE
Keywords: Dolomite; Silurian Period; Stratigraphy; Jarosite